Analysis of Superconducting Fault Current Limiterin DC System with Renewable Energy Sources - S. Sanjeeva Rayudu; C. Ganesh; B. Vignesh Naik (Institute of Advanced Engineering and Science, 2016)
Superconducting fault-current limiters (SFCLs) have been the subject of research and development for many years and offer an attractive solution to the problem of rising fault levels in electrical distribution systems. SFCLs can greatly reduce fault currents and the damage at the point of fault, and help improve the stability of a power system. Superconducting fault-current limiters (SFCL) provide a new efficient approach to the reliable handling of such faults.(SCFLs) can be used for various nominal voltages and currents, and can be adapted to particular limiting characteristics in case of short circuits. In this project, dc resistive type superconducting fault current limiter (SFCL) is presented. This SFCL is designed for the HVDC system. Uniform current and voltage sharing among the SFCL modules can be observed through contact resistance tests, dc flow-through tests, and ac flow-through tests. Results of tests show that each limiting module has good uniformity in higher current system. The proposed concept can be implemented using renewable energy sources.The results are presented by using Matlab/Simulink platform.